Fanconi anemia with biallelic FANCD1/BRCA2 mutations - Case report of a family with three affected children - Svojgr, Karel; Sumerauer, David; Puchmajerova, Alena; Vicha, Ales; Hrusak, Ondrej; Michalova, Kyra; Malis, Josef; Smisek, Petr; Kyncl, Martin; Novotna, Drahuse; Machackova, Eva; Jencik, Jan; et al. (European journal of medical genetics, 2016)
Fanconi anemia, complementation group D1 with bi-allelic FANCD1 (BRCA2) mutations, is a very rare genetic disorder characterized by early onset of childhood malignancies, including acute leukemia, brain cancer and nephroblastoma. Here, we present a case report of a family with 3 affected children in terms of treatment outcome, toxicity and characterization of the malignancies using comprehensive cytogenetic analysis. The first child was diagnosed with T-cell acute lymphoblastic leukemia when he was 11 months old. During chemotherapy, he suffered from repeated pancytopenia, sepsis and severe vincristine polyneuropathy, and 18 months after primary diagnosis, he succumbed to secondary acute monocytic leukemia. The second child was diagnosed with stage 2 triphasic nephroblastoma (Wilms tumor), when he was 3 years and 11 months old. During chemotherapy, he suffered from vincristine polyneuropathy. Currently, he is in complete remission, 29 months following the initial diagnosis. The third child was diagnosed with medulloblastoma with classical histology, when she was 4 years and 5 months old. After the first cycle of chemotherapy, she suffered from prolonged pancytopenia, sepsis and severe skin and mucosal toxicity. Six weeks after primary diagnosis, a first relapse in the posterior fossa was diagnosed, and at 7 and half months after primary diagnosis, a second relapse was diagnosed that led to the patient's death. Our case report underscores tumor heterogeneity, treatment toxicity and poor outcome in Fanconi anemia patients of complementation group D1.
Keywords: Magnetic Resonance Imaging; Fanconi Anemia; Female; Phenotype; rodina; předškolní dítě; ženské pohlaví; jednonukleotidový polymorfismus; Fanconiho anemie; lidé; Polymorphism, Single Nucleotide; magnetická rezonanční tomografie; Antineoplastic Combined Chemotherapy Protocols; protein BRCA2; Loss of Heterozygosity; Immunophenotyping; protokoly protinádorové kombinované chemoterapie; imunofenotypizace; Male; ztráta heterozygozity; Child, Preschool; Family; hybridizace in situ fluorescenční; fenotyp; mužské pohlaví; In Situ Hybridization, Fluorescence; BRCA2 Protein; Humans